2008
DOI: 10.1158/0008-5472.can-07-6849
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Metastatic Outgrowth from Single Dormant Tumor Cells by Targeting the Cytoskeleton

Abstract: Metastatic breast cancer may emerge from latent tumor cells that remain dormant at disseminated sites for many years. Identifying mechanisms regulating the switch from dormancy to proliferative metastatic growth has been elusive due to the lack of experimental models of tumor cell dormancy. We characterized the in vitro growth characteristics of cells that exhibit either dormant (D2.0R, MCF-7, and K7M2AS1.46) or proliferative (D2A1, MDA-MB-231, and K7M2) metastatic behavior in vivo. Although these cells prolif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
394
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(421 citation statements)
references
References 45 publications
27
394
0
Order By: Relevance
“…Phalloidin staining further verified a significant difference in the cell shape and distribution of F-actin, implying that ERp29-transfected MDA-MB-231 cells underwent cytoskeletal reorganization with loss of filamentous stress fibers and cortical actin formation (Figure 3b). Concomitantly, the extracellular matrix (ECM) component FN, which is involved in cell transition from quiescence to proliferation, 29 was decreased in ERp29-transfected MDA-MB-231 cells, as shown by immunofluorescent staining (Figure 3c). Importantly, we observed that epithelial cell marker E-cadherin was highly expressed in both clone B and E cells and its membranous distribution is identical to that observed in MCF-7 cells (Figure 3d).…”
Section: Erp29 Regulates Mesenchymal-epithelial Transition In Mda-mb-mentioning
confidence: 89%
See 1 more Smart Citation
“…Phalloidin staining further verified a significant difference in the cell shape and distribution of F-actin, implying that ERp29-transfected MDA-MB-231 cells underwent cytoskeletal reorganization with loss of filamentous stress fibers and cortical actin formation (Figure 3b). Concomitantly, the extracellular matrix (ECM) component FN, which is involved in cell transition from quiescence to proliferation, 29 was decreased in ERp29-transfected MDA-MB-231 cells, as shown by immunofluorescent staining (Figure 3c). Importantly, we observed that epithelial cell marker E-cadherin was highly expressed in both clone B and E cells and its membranous distribution is identical to that observed in MCF-7 cells (Figure 3d).…”
Section: Erp29 Regulates Mesenchymal-epithelial Transition In Mda-mb-mentioning
confidence: 89%
“…As the cell shape and cytoskeletal configuration have a critical role in regulating the transition of cells from a nonproliferative to a proliferative state, 4,29,38 the ERp29-mediated cytoskeletal reorganization in proliferative MDA-MB-231 cells indicated ERp29 as a novel regulator in inducing cell dormancy. This is further supported by the identical phenotype between ERp29-transfected MDA-MB-231 cells and dormant MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…When placed on BME, the dormant cell lines remain as single cells and do not proliferate, suggesting that the extracellular matrix plays a role in preserving the dormant state. 16 This assay has been useful for identifying mechanisms and pathways that regulate dormancy, and it provides a useful tool for screening and evaluating therapeutics in vitro. 50 This assay can also be used with heterogeneous cancer cell lines in limiting dilution cultures on BME to identify and isolate subpopulations of nondividing dormant cells as mentioned above.…”
Section: Dormancy Assaymentioning
confidence: 99%
“…14 Other assays based on cancer cell morphology, clonogenicity, growth, and dormancy on the matrix have also been developed more recently. 15,16 Coinjection of the basement membrane-like matrix with cancer cells either subcutaneously or in orthotopic sites was found to increase both the 'take' and growth of tumors in mice. [17][18][19] Thus, cancer cell interactions with the basement membrane have multiple uses both in vitro and in vivo (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…The role of ERp29 in regulating p38 expression and phosphorylation was further verified in MCF-7 cells, which show a dormant-like state in three-dimensional cell cultures. 31 As shown in Figure 2c, knockdown of ERp29 resulted in a significant reduction of p-p38 (3-fold, Po0.01) and upregulation (1.8-fold, Po0.05) of basal p38a. Furthermore, ERp29 knockdown in MCF-7 cells significantly increased FAK expression (B2.3-fold, Po0.01) and phosphorylation (B2.9-fold, Po0.01) relative to these cells treated with scrambled control shRNA (shCtrl; Figure 2c).…”
Section: Overexpression Of Erp29 Activates P38 Phosphorylation and Dementioning
confidence: 65%